Efektivitas dan Efek Samping pada Terapi Multi-Drug-Resistant Tuberculosis (MDR-TB): Kajian Literatur - Sanjaya, Dwi Arymbhi; Meriyani, Herleeyana; Juanita, Rr. Asih; Siada, Nyoman Budiartha; Noviani, Lusy (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
Multi-drug-resistant tuberculosis (MDR-TB) leads to a reduced cure rate for tuberculosis treatment. The global number of MDR-TB cases remained relatively stable between 2015 and 2020 but increased in 2021. In 2020, the World Health Organization (WHO) estimated 437,000 MDR-TB cases worldwide, which rose to 450,000 cases in 2021. Various treatment regimens recommended by the WHO require a review of the literature on the efficacy and side effects of drug use in MDR-TB. This review aims to provide updated information that can be used as a reference for the early identification and management of side effects. The article was a narrative review that collected and analyzed information from various international articles on databases such as PubMed, PlosOne, and ScienceDirect from January 2014 to June 2024. A total of six relevant articles were synthesized from 609 articles. The effectiveness of MDR-TB therapy with WHO-recommended drugs has shown a high cure rate (cured>50%). The incidence of side effects in MDR-TB therapy is smaller compared to the effectiveness of treatment. However, a study conducted at Wuhan Jinyintan Hospital in China from July 2019 to December 2020 showed that all study subjects experienced side effects. This included nausea and vomiting from protionamide, gatifloxacin, and ethambutol; hyperuricemia from pyrazinamide, and hyperpigmentation from clofazimine. It is recommended that a therapy regimen be selected based on culture test results, patient conditions, and drug availability in each country.